Strategic entrepreneurship in the future: Theoretical views - Martinović Milan; Martinović Saša (Trendovi u Poslovanju)
The paper describes the role and importance of strategy in contemporary entrepreneurship, which operates under conditions of rapid change. Strategic Enterprise includes a set of entrepreneurial actions undertaken for the purpose of strategic perspective. It describes the key characteristics of modern entrepreneurs with strategic emphasis on the needs of the strategic analysis of business opportunities and possibilities of business enterprises in the specific conditions, at the beginning of the third millennium.